The p53 Transcriptional Network Influences Microglia Behavior and Neuroinflammation - Aloi, Macarena S. (Crit Rev Immunol, 2015)
The tumor-suppressor protein p53 belongs to a family of proteins that play pivotal roles in multiple cellular functions including cell proliferation, cell death, genome stability, and regulation of inflammation. Neuroinflammation is a common feature of central nervous system (CNS) pathology, and microglia are the specialized resident population of CNS myeloid cells that initiate innate immune responses. Microglia maintain CNS homeostasis through pathogen containment, phagocytosis of debris, and initiation of tissue-repair cascades. However, an unregulated pro-inflammatory response can lead to tissue injury and dysfunction in both acute and chronic inflammatory states. Therefore, regulation of the molecular signals that control the induction, magnitude, and resolution of inflammation are necessary for optimal CNS health. We and others have described a novel mechanism by which p53 transcriptional activity modulates microglia behaviors in vitro and in vivo. Activation of p53 induces expression of microRNAs (miRNAs) that support microglia pro-inflammatory functions and suppress anti-inflammatory and tissue repair behaviors. In this review, we introduce the previously described roles of the p53 signaling network and discuss novel functions of p53 in the microglia-mediated inflammatory response in CNS health and disease. Ultimately, improved understanding of the molecular regulators modulated by p53 transcriptional activity in microglia will enhance the development of rational therapeutic strategies to harness the homeostatic and tissue repair functions of microglia.